Research of the peculiarities of enterpises՚ work organization in the intercultural space - M. A. Gil Martínez; Yu. V. Vorontsova (Управление)
The article is devoted to the study of the organization of the work of enterprises in the intercultural space. The authors consider the cross-cultural approach as a cross-cutting process that leads to significant changes within organizations and society and which manifests itself through interaction that functions as a generating element of the exchange of ideas and knowledge. Culture becomes the driving force of the processes taking place in international companies, where people interact freely, focusing on achieving common goals of their development, understanding their own characteristics and differences, which inevitably leads to high productivity of the organization and increased motivation of its partners.The paper considers the management of the organization’s cross-cultural space in the context of three main elements: cross-culturality, competencies and interaction in the workplace. In the course of their activities, enterprises are faced with the peculiarities of the organization of work in an intercultural space, which, as a rule, consist in the mental differences of business representatives of different cultures. In the process of interaction, difficulties may arise due to the lack of a deep understanding of the ethnic characteristics of the partner, its history, culture, etc. In this regard, the authors recommend pay attention to the quality of the acquired cross-cultural competencies of the participants of the business dialogue. Organizations should invest in the cross-cultural knowledge of their employees to increase the efficiency and productivity of internationally organized businesses.Modern organizations tend to view business processes as knowledge processes. The creation of knowledge includes its further expansion, development, improvement and application in the organization. Modern business organizations are looking for ways to create additional knowledge values through identifying, applying, and using them in a unique way, and this is a process that is part science, part art, and part pure luck. Effective management of the knowledge that people from different cultures bring, as well as the spaces in which they will interact, сontribute to strengthening the corporate image of the organization and its positioning in the international market.